Path regularity for stochastic differential equations in Banach spaces - Dettweiler, Johanna (KIT Scientific Publishing, 2007)
In this work we analzyse the Stochastic Cauchy Problem driven by a cylindrical Wiener process. Given the existence of solutions we show regularity of the paths of the solution. In dependence on properties of the operators in the equation or on geometrical properties of the underlying Banachspace we derive space time regularity results for the paths of the solution.